Design of Novel Nanogel Formulation of Naproxen Sodium for Enhanced Anti-inflammatory Effect - Jadhav, Dr. Khanderao R. (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The main aim and objective of this project study are to developed the nanogel of naproxen sodium and evaluate them. Naproxen sodium has been used as non-steroidal anti-inflammatory drug (NSAID’s) for its anti-inflammatory and analgesic effect. Topical NSAIDs will penetrate the skin and help reduce pain locally. Oral route causes irritation and ulceration of GIT to avoid this reaction naproxen sodium given topically. The aim of the present study is to formulate naproxen sodium-loaded nanodispersion and then incorporated into a gelling agent to produce nanogel which will improve solubility as well as skin permeation of drug. Materials and Methods: Formulations were developed with varying concentrations of polymers like Eudragit RS100 and sodium alginate using modified emulsification-diffusion method. Differential scanning calorimetric and Fourier transforms infrared (FTIR) analysis was performed to ensure the compatibility of the drug and excipients. The gels were tested for clarity, viscosity, spreadability, surface pH, drug content uniformity, in vitro drug diffusion study, and skin irritation study using rat abdominal skin. Results: FTIR studies showed no evidence on interactions between drug, polymers, and excipients. The formulations are characterized for the particle size and found to be below 150 nm. The drug content in the formulations was found satisfactory. The best in vitro drug release profile was achieved with the formulation F4 batch exhibited 6 h sustained drug release, that is, 93.05% with desired therapeutic concentration which contains the drug. The formulation showed optimum stability and possessed a sustained drug release during the study period. The nanogel formulation showed the favorable alternative to oral administration for naproxen sodium. Conclusion: From the overall study, it was conclud